Comparison of Mediation and Litigation in Dispute Resolution: The Impact of Culture on Fairness and Acceptability of Outcomes in Multicultural Societies - Saputra, Rio; Pakpahan, Novritsar Hasitongan; Hardyansah, Rommy; Darmawan, Didit; Dirgantara, Febrian (Journal of Social Science Studies, 2022)
Dispute resolution is very important to maintain harmony in society, especially in a multicultural society. This article examines a comparison between two commonly used dispute resolution methods, mediation and litigation, with a focus on their impact on social relations, costs, and acceptance of the settlement outcome by all parties involved. Cultural differences play a significant role in determining the most appropriate method for each social group. Mediation, with its emphasis on consensus and rapprochement, is more acceptable in societies that prioritize social harmony, while litigation, with its formal processes and more structured justice, is preferred in cultures that emphasize authority and legal certainty. Success in dispute resolution depends largely on the ability to adapt methods to the cultural values of the society in question. A legal system that is inclusive and sensitive to cultural differences can enhance the fairness and acceptability of dispute resolution outcomes. An understanding of cultural differences and increased training for legal practitioners and mediators are needed to create fair and effective dispute resolution processes in multicultural societies.